2001
DOI: 10.1046/j.1525-1438.2001.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle proteins as molecular markers of malignant change in vulvar lichen sclerosus

Abstract: Lichen sclerosus (LS) has a known association with the development of squamous cell carcinoma of the vulva. The purpose of this study was to investigate molecular markers, which could indicate premalignant changes. Multiple sequential vulvar biopsies were taken over a period of 11 years from a patient with longstanding LS. Immunohistochemical staining was used to demonstrate a range of molecular markers. Increased expression of p53 and Ki67 was found in areas of squamous hyperplasia (SH) and differentiated vul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

2002
2002
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 15 publications
(17 reference statements)
0
14
0
4
Order By: Relevance
“…27 Only scoring the MIB1 pattern or using a semiquantitative scoring method is less accurate. 28 Owing to deep rete pegs the measurement of the entire epithelium, as previously published by Bulten et al 15 for cervical lesions, is technically not possible in differentiated VIN lesions. We calculated the MIB1 positivity index by dividing the measured MIB1-positive nuclear area by the total nuclear area.…”
Section: Discussionmentioning
confidence: 99%
“…27 Only scoring the MIB1 pattern or using a semiquantitative scoring method is less accurate. 28 Owing to deep rete pegs the measurement of the entire epithelium, as previously published by Bulten et al 15 for cervical lesions, is technically not possible in differentiated VIN lesions. We calculated the MIB1 positivity index by dividing the measured MIB1-positive nuclear area by the total nuclear area.…”
Section: Discussionmentioning
confidence: 99%
“…The IHC procedure has been described previously (Rolfe et al, 2001(Rolfe et al, , 2002. Briefly, sections were dewaxed in xylene and rehydrated through different grades of ethanol up to distilled water.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…It has previously been demonstrated that there is increased cell proliferation in LS and LS adjacent to SCC (Rolfe et al, 2001(Rolfe et al, , 2002 and there may therefore be an increased likelihood of a spontaneous mutation (Hietanen et al, 1995). Inflammatory processes may also be involved in oxidative damage caused by free radicals (Carlson et al, 1998).…”
Section: Tp53 Mutation Profile In Sccmentioning
confidence: 99%
“…Thus, expression of cyclin D1 was shown to be overexpressed in 51% of squamous cell carcinomas and in 50% of lichen sclerosus but only in 31% of SCH. 3 Similarly, loss of pRb expression was shown to occur in lichen sclerosus at a percentage (40%) more similar to the one observed in squamous cell carcinomas (37%) than in SCH (62%). 3 Similar results have been also reported for p53 expression and mutations 29,30 and a similar trend was previously observed for COX-2 expression.…”
Section: Discussionmentioning
confidence: 72%
“…Thus, an increased expression of p53 and Ki67 was reported to accompany histologic changes in the progression of vulvar premalignant lesions to malignancy. 3 On the other hand, a progressive loss of pRb, pRb2/p130 and of the CDK inhibitor p16 INK4 from benign lesions to invasive squamous cell carcinomas of the vulva has been reported [4][5][6] thus suggesting a role for these molecules in vulvar carcinogenesis.…”
mentioning
confidence: 99%